Surface Gravity Information of Nepal and its Role in Gravimetric Geoid Determination and Refinement (Journal on Geoinformatics, Nepal, 2010)
This paper describes proposed first order gravity network which was almost abandoned and existing gravity database that has to be preserved and advocates about its importance in the determination of regional gravimetric geoid of the country. Since GPS is in full phase operation and adopted as an efficient and accurate method in position and height determination the paper also elaborates how all its three components can be taken into consideration.